Green supply chain integration, supply chain agility and green innovation performance: Evidence from Chinese manufacturing enterprises - Zhang, Bochen; Zhao, Shukuan; Fan, Xueyuan; Wang, Shuang; Shao, Dong (Frontiers in Environmental Science, 2022)
Despite widespread attention on the significance of green supply chain integration (GSCI), there is still limited research on how GSCI can improve firms' green innovation performance. From the perspective of the natural resource-based view and dynamic capability theory, based on the theoretical logic of "resource-capability-performance", this study aims to explore the relationship between GSCI and firms' green innovation performance and its intrinsic mechanism. In order to test the research model, this study collected survey data from 405 Chinese manufacturing firms and tested them by using hierarchical regression and bootstrap analysis. The results show that all three dimensions of GSCI, namely, green internal integration, green supplier integration, and green customer integration, have positive effects on supply chain agility. In addition, supply chain agility has a significant positive impact on green product and process innovation. This study also finds that supply chain agility plays a partially mediating role between all three dimensions of GSCI and green product and process innovation; that is, GSCI can further promote firms' green innovation performance by improving supply chain agility. The results of this study not only enrich the theoretical research on the driving factors of firms' green innovation but also provide policy implications for manufacturing firms and government policy-makers regarding the implementation and promotion of green innovation practices.